Donkey Skin Trade and Its Non-compliance With Legislative Framework - Lima, Yuri Fernandes; Tatemoto, Patricia; Reeves, Emily; Burden, Faith Adelaide; Santurtun, Eduardo (Frontiers in Veterinary Science, 2022)
Donkeys (Equus asinus) are facing a global crisis. Their welfare, and even survival, is being compromised as the demand for their skins increases. This demand is driven by the need to supply raw materials to produce ejiao, a Traditional Chinese Medicine made from collagen extracted from donkey skins. Since there is no productive chain for donkey skin production outside of China, the global trade is an entirely extractive industry that has resulted in the decimation of some local donkey populations. The donkey skin trade is demonstrably unsustainable, from the ethical issues associated with poor welfare, to the biosecurity and human health risks the trade poses; and it violates both legal frameworks and moral expectations at both a national and global level.